Pengaruh Dana Pihak Ketiga, CAR, NPL, BI Rate, Inflasi dan Nilai Tukar Mata Uang terhadap Profitabilitas Bank Umum Persero Tahun 2007-2018 - Sudarjah, Gugum Mukdas; Priadana, Sidik; Pratama, Reza Anugrah (Ridwan Institute, 2021)
The Bank is a business entity that in its business activities raises funds from the community and its mines in the form of credit. As for the banking structure in Indonesia, it consists of commercial banks and BPR. Adaris main commercial banks and BPR what no one is in a way of depositing giro and can not also be cross-payment, can not be in-activities in foreign exchange and limited stage operations. This research is an expectation to know the Macroeconomics and Internal Performance performance of Bank Persero and BPD for the period 2007-2018 and to know how the influence of Third Party Funds, CAR, NPL, BI Rate, Inflation and Exchange Rate on the Profitability of Bank Persero and BPD. The sample in this study is Persero Commercial Bank. This study uses descriptive and verificative methods. Data analysis then which way of analysis data panel regression. The results of the study point that Simultaneously has 3 variables of positive, but uneven relationships, namely CAR, DPK, and BI Rate. As for npl variables and exchange rates have a good relationship and exchange rate results. When viewed from the coefficient value of each variable, then the VARIABLE NPL and Exchange Rate have a considerable influence on the performance of profitability.